PENGARUH KUALITAS LAYANAN DAN PROMOSI TERHADAP KEPUASAN KONSUMEN MAXXBOX - Ivantan Ivantan; Dede Solihin (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2026)
This study aims to analyze the role of service quality and promotion in shaping consumer satisfaction at Maxxbox Lippo Village Karawaci. The research employs an associative approach, with the population consisting of all visitors, and a sample of 100 respondents determined using the Slovin formula. The data analysis technique applied is multiple linear regression to examine both partial and simultaneous relationships among variables. The results indicate that service quality plays a crucial role in enhancing consumer satisfaction, as reflected in its ability to provide comfort, build trust, and create positive experiences for visitors. In addition, promotion also contributes significantly to shaping satisfaction, particularly through the attractiveness of information, the offers provided, and its ability to enhance consumers’ perceived value. Simultaneously, service quality and promotion demonstrate a stronger combined effect on increasing consumer satisfaction, indicating that both variables complement each other.